1991
DOI: 10.1515/jpme.1991.19.6.485
|View full text |Cite
|
Sign up to set email alerts
|

Is placenta previa a determinant of preeclampsia?

Abstract: Low implantation of the placenta has been reported to be associated with a decreased risk for preeclampsia and this has been attributed to increased placental blood flow. However, placenta previa is known to be associated with separation and bleeding, intrauterine growth retardation, and elevated umbilical blood flow resistance by Doppler studies, suggesting decreased umbilical blood flow. To better evaluate the relationship of placenta previa and preeclampsia, 6576 consecutive patients who had ultrasound exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…However, the present data provides indirect evidence that the oxygen demands of the placenta and developing fetus of women with placenta previa are most frequently reached when trophoblast penetration of the lower uterine segment myometrium is appropriate. The observation that women with placenta previa and physiologic myometrial invasion have a normal serological profile of VEGF, PlGF and sFlt-1, is consistent with none of the fetuses in our cohort being growth restricted and with the literature refuting placenta previa as an independent risk factor for IUGR or preeclampsia 33,34…”
Section: Commentsupporting
confidence: 91%
“…However, the present data provides indirect evidence that the oxygen demands of the placenta and developing fetus of women with placenta previa are most frequently reached when trophoblast penetration of the lower uterine segment myometrium is appropriate. The observation that women with placenta previa and physiologic myometrial invasion have a normal serological profile of VEGF, PlGF and sFlt-1, is consistent with none of the fetuses in our cohort being growth restricted and with the literature refuting placenta previa as an independent risk factor for IUGR or preeclampsia 33,34…”
Section: Commentsupporting
confidence: 91%
“…Some other studies had reported a 50% reduction in pre-eclampsia in these women (12). Jelsema did not find any relationship between placenta previa and the incidence of pre-eclampsia (13). In all mentioned studies, the sample size was small, and therefore designing a meta-analysis study can offer reliable results about the association between placenta previa and pre-eclampsia.…”
Section: Introductionmentioning
confidence: 91%
“…Three studies were case-control (8,17,18), five studies were cohort (13,(19)(20)(21)(22), and one study was cross-sectional (23). The total sample size in the present meta-analysis was 752,243 participants.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…There have been inconsistent findings with respect to the relationship between PE and PP: Ananth et al[ 8 ] reported in 1997 that the presence of PP could reduce the incidence of PE by 50%. However, Hasegawa and Adam[ 4 , 5 ], found no cases of PE present in women with PP, and Jelsema [ 9 ]reported that the presence of PP did not lower the incidence of PE. However, the sample sizes of these studies were small, with numbers of PP cases ranging from 200 to 300 [ 4 , 5 , 8 , 10 ], and most of these studies did not take into consideration the influence of interfering factors such as BMI on the results of the study [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%